64.1k views
5 votes
Use completing the square to solve for x in the equation (x minus 12) (x + 4) = 9. x = –1 or 15 x = 1 or 7 x = 4 plus-or-minus StartRoot 41 EndRoot x = 4 plus-or-minus StartRoot 73 EndRoot

User Ajil Mohan
by
4.6k points

2 Answers

6 votes

Answer:

EDGE2020 Option D :}

Explanation:

User Mquemazz
by
4.2k points
3 votes

Answer:

x = 4 ±
√(73)

Explanation:

Given

(x - 12)(x + 4) = 9 ← expand the left side using FOIL

x² - 8x - 48 = 9 ( ad 48 to both sides )

x² - 8x = 57

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- 4)x + 16 = 57 + 16

(x - 4)² = 73 ( take the square root of both sides )

x - 4 = ±
√(73) ( add 4 to both sides )

x = 4 ±
√(73)

User Dblood
by
4.9k points